Gender as a risk factor for adverse intraoperative and postoperative outcomes of elective pancreatectomy. Issue 2 (4th November 2016) - Mazmudar, Aditya; Vitello, Dominic; Chapman, Mackenzie; Tomlinson, James S.; Bentrem, David J.
Abstract : Background and Objectives: Patient selection remains paramount when developing and adopting quality‐based assessment and reimbursement models, and enhanced recovery protocols. Gender is a patient characteristic known before surgery which can inform risk stratification. Our aim was to evaluate the effect of gender on intraoperative blood transfusions, operative time, length of hospital stay, estimated blood loss (EBL) as well as postoperative surgical site infections (SSIs), and mortality. Methods: Patients undergoing elective pancreatectomy from 2005 to 2013 were identified in the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP) and Northwestern institutional databases. Multivariable analyses were conducted to identify the association between gender and these outcomes. Results: Analyses demonstrated that male gender was independently associated with blood transfusion (OR 1.23), operative time >6 hr (OR 1.76), length of stay greater than 11 days (OR 1.17), and all‐type SSIs (OR 1.17), especially superficial SSIs (OR 1.15) and organ space SSIs (OR 1.18). Analysis of the institutional cohort found that male gender was independently associated with increased odds of EBL > 1 L for Whipple procedures (OR 2.85). Conclusions: Male gender is a significant predictor of increased operative time, length of stay, transfusions, EBL > 1L, as well as postoperative organ space surgical site infections in these patients. J. Surg. Oncol. 2017;115:131–136 . © 2016 Wiley Periodicals, Inc.